2005
DOI: 10.1086/427540
|View full text |Cite
|
Sign up to set email alerts
|

"Sculptor-ing" the Galaxy? The Chemical Compositions of Red Giants in the Sculptor Dwarf Spheroidal Galaxy

Abstract: We used high-resolution, high signal-to-noise ratio spectra obtained with the Very Large Telescope and the UVVisual Echelle Spectrograph to determine abundances of 17 elements in four red giants in the Sculptor (Scl ) dwarf spheroidal galaxy. Our ½Fe=H -values range from À2.10 to À0.97, confirming previous findings of a large metallicity spread. We combined our data with similar data for five Scl giants studied recently by Shetrone et al. to form one of the largest samples of high-resolution abundances yet obt… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

28
252
2
1

Year Published

2009
2009
2015
2015

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 189 publications
(284 citation statements)
references
References 99 publications
28
252
2
1
Order By: Relevance
“…The spread in stellar chemical abundances, and in particular the low [α/Fe] values compared to Galactic halo stars at equal metallicity, are hardly compatible with an early termination of star formation at the epoch of reionization (e.g., Harbeck et al 2001; Shetrone et al 1998Shetrone et al , 2001Shetrone et al , 2003Tolstoy et al 2003;Geisler et al 2005; Koch et al 2008, examples taken in relation to the galaxies studied in this work). Whilst some dSphs are indeed consistent with rather short star formation episodes, such as Sextans (Lee et al 2003) or Sculptor (Babusiaux et al 2005), others are characterized by much more extended periods, like Carina (Smecker-Hane et al 1996;Hurley-Keller et al 1998) or Fornax (Coleman & de Jong 2008).…”
Section: Introductionmentioning
confidence: 57%
“…The spread in stellar chemical abundances, and in particular the low [α/Fe] values compared to Galactic halo stars at equal metallicity, are hardly compatible with an early termination of star formation at the epoch of reionization (e.g., Harbeck et al 2001; Shetrone et al 1998Shetrone et al , 2001Shetrone et al , 2003Tolstoy et al 2003;Geisler et al 2005; Koch et al 2008, examples taken in relation to the galaxies studied in this work). Whilst some dSphs are indeed consistent with rather short star formation episodes, such as Sextans (Lee et al 2003) or Sculptor (Babusiaux et al 2005), others are characterized by much more extended periods, like Carina (Smecker-Hane et al 1996;Hurley-Keller et al 1998) or Fornax (Coleman & de Jong 2008).…”
Section: Introductionmentioning
confidence: 57%
“…also include, for comparison, Galactic stars from the compilation of Venn et al (2004;and references therein) and Milky Way dSph satellites including the more luminous dSphs (Shetrone et al 2001(Shetrone et al , 2003(Shetrone et al , 2009Fulbright et al 2004;Sadakane et al 2004;Geisler et al 2005;Aoki et al 2009;Cohen & Huang 2009;Frebel et al 2010a;Letarte et al 2010;Tafelmeyer et al 2010;Lemasle et al 2012;Venn et al 2012;and Starkenburg et al 2012) and the most recent measurements in a few ultrafaint dSphs (K08; Feltzing et al 2009;Frebel et al 2010b;Norris et al 2010b;Simon et al 2010;and Gilmore et al 2013). The Ba abundances and limits are very low, at a mean [Ba/H] of −3.97 from the three EW measurements, and [Ba/H] < −3.84 (2σ), <−3.55 (3σ), respectively.…”
Section: Resultsmentioning
confidence: 99%
“…The shaded areas represent the expected age ranges of star formation as indicated by photometric studies. Geisler et al, 2005;Hill et al, 2011) are shown as small green dots and Milky Way halo stars as small grey dots. …”
Section: Discussionmentioning
confidence: 99%